Analisis Bisnis Model Canvas Pada Operator Jasa Online Ride-Sharing Noompang - Fitri Yusnita; Nidya Novalia; Amalia Darawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
Innovation in the transportation sector with the principle of sharing economy has created a new service industry sector, namely online ride-sharing services. Companies can display in a simple but comprehensive manner the nine essential components of a business. A business model is a method that helps companies tell stories about the internal conditions of the company. This study aims to analyze the business model of Noompang using the Business Model Canvas analysis. This research uses descriptive-exploratory method. Data collection using the ghost interview method to the selected driver. Data obtained from interviews with partners, both drivers and passengers Noompang in Bandung - Jakarta and the results of studies of supporting literature. The results obtained from this study are that Noompang benefits from profit sharing with partner companies, profit sharing with driver partners, benefits from the Ovo e-wallet, and benefits from Google / Apple on application downloads.